An Analysis of Factors Affecting Speaking Confidence of Secondary School Students at UPT SMA Negeri 1 Sidrap - Muhammad Anugrah Nasruddin; H. Syamsu T; Nurul Faradillah; Ibrahim Manda; Sam Hermansyah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to identify and analyze the factors influencing the speaking confidence of secondary school students at UPT SMA Negeri 1 Sidrap. This research employed a descriptive qualitative approach focusing on students’ experiences and perceptions in the process of learning English. The participants of the study were eleventh-grade students selected through purposive sampling. The data were collected through questionnaires, semi-structured interviews, and documentation to obtain comprehensive information regarding the factors affecting students’ speaking confidence. The findings reveal that students’ speaking confidence is influenced by two main categories of factors, namely internal factors and external factors. Internal factors include language proficiency, previous speaking experience, and psychological aspects such as self-confidence, anxiety, and personality. Meanwhile, external factors include the teacher’s role, teaching methods, learning materials and media, peer support, and classroom atmosphere. The analysis demonstrates that students' speaking confidence is fundamentally influenced by the interplay of internal and external dimensions. Internally, the primary obstacles originate from linguistic deficiencies (specifically in vocabulary and grammar) alongside psychological barriers such as shyness and apprehension. Conversely, externally, the teacher's pedagogical approach and instructional methods emerge as the most impactful drivers. The integration of creative media and a supportive classroom climate significantly mitigate the fear of social judgment, thereby lowering students' internal anxiety. In conclusion, while internal readiness poses a challenge, a safe and encouraging external environment serves as the vital catalyst for improving students' confidence in oral English communication.